Study on isolation improvement between closely‐packed patch antenna arrays based on fractal metamaterial electromagnetic bandgap structures. Issue 14 (11th October 2018) - Alibakhshikenari, Mohammad; Virdee, Bal S.; See, Chan H.; Abd‐Alhameed, Raed; Hussein Ali, Ammar; Falcone, Francisco; Limiti, Ernesto
Abstract : A decoupling metamaterial (MTM) configuration based on fractal electromagnetic‐bandgap (EMBG) structure is shown to significantly enhance isolation between transmitting and receiving antenna elements in a closely‐packed patch antenna array. The MTM‐EMBG structure is cross‐shaped assembly with fractal‐shaped slots etched in each arm of the cross. The fractals are composed of four interconnected‐'Y‐shaped' slots that are separated with an inverted‐'T‐shaped' slot. The MTM‐EMBG structure is placed between the individual patch antennas in a 2 × 2 antenna array. Measured results show the average inter‐element isolation improvement in the frequency band of interest is 17, 37 and 17 dB between radiation elements #1 & #2, #1 & #3, and #1 & #4, respectively. With the proposed method there is no need for using metallic‐via‐holes. The proposed array covers the frequency range of 8–9.25 GHz for X‐band applications, which corresponds to a fractional‐bandwidth of 14.5%. With the proposed method the edge‐to‐edge gap between adjacent antenna elements can be reduced to 0.5λ0 with no degradation in the antenna array's radiation gain pattern. Across the array's operating band, the measured gain varies between 4 and 7 dBi, and the radiation efficiency varies from 74.22 and 88.71%. The proposed method is applicable in the implementation of closely‐packed patch antenna arrays used in SAR and MIMO systems.